Glimpses of Mughal society and culture : a study based on Urdu literature, in the 2nd half of the 18th century - Haque, Ishrat, 1948- (New Delhi : Concept, 1992)
Social conditions of Mogul Empire as depicted in Urdu poetry of 18th century.
Includes index.
Keywords: Urdu poetry -- 1500-1800 -- History and criticism